V1a vasopressin receptors maintain normal blood pressure by regulating circulating blood volume and baroreflex sensitivity - Koshimizu, Taka-aki (National Academy of Sciences, 2006)
Arginine-vasopressin (AVP) is a hormone that is essential for both osmotic and cardiovascular homeostasis, and exerts important physiological regulation through three distinct receptors, V1a, V1b, and V2. Although AVP is used clinically as a potent vasoconstrictor (V1a receptor-mediated) in patients with circulatory shock, the physiological role of vasopressin V1a receptors in blood pressure (BP) homeostasis is ill-defined. In this study, we investigated the functional roles of the V1a receptor in cardiovascular homeostasis using gene targeting. The basal BP of conscious mutant mice lacking the V1a receptor gene (V1a(−/−)) was significantly (P < 0.001) lower compared to the wild-type mice (V1a(+/+)) without a notable change in heart rate. There was no significant alteration in cardiac functions as assessed by echocardiogram in the mutant mice. AVP-induced vasopressor responses were abolished in the mutant mice; rather, AVP caused a decrease in BP, which occurred in part through V2 receptor-mediated release of nitric oxide from the vascular endothelium. Arterial baroreceptor reflexes were markedly impaired in mutant mice, consistent with a loss of V1a receptors in the central area of baroreflex control. Notably, mutant mice showed a significant 9% reduction in circulating blood volume. Furthermore, mutant mice had normal plasma AVP levels and a normal AVP secretory response, but had significantly lower adrenocortical responsiveness to adrenocorticotropic hormone. Taken together, these results indicate that the V1a receptor plays an important role in normal resting arterial BP regulation mainly by its regulation of circulating blood volume and baroreflex sensitivity.